Municipalities And Health – Citizens' Expectations About Local Health Policies - Angelika Velkova; Paulina Kirova (Journal of Biomedical & Clinical Research, 2015)
The aim of this study was to explore citizens' expectations about local health policies in order to create an adequate strategy. Local authorities in many countries place health in the core of their strategic planning aiming to create and improve a health-supporting social and physical environment, as they usually have primary responsibility for planning and/or delivering many of the services that are crucial to addressing the social determinants of health. Local health policies are created in consultation with local health services, NGOs and citizens. The survey was conducted among 400 citizens of Pleven Municipality. Of these, 335 (83.75%) responded to the invitation. Information on health problems and determinants of health was collected through a direct inquiry survey. The majority of citizens considered the impact of environmental, educational, cultural and economic factors as well as public security on their health. They expected that more purposeful efforts of the local authorities be directed for improving living conditions and inequalities in health. The citizens are willing to work together with municipalities to create health policies, which reduce negative factors and increase positive ones. They are aware that local policies and decisions have a very significant impact on the economic, social and environmental factors affecting health and well-being and therefore municipalities play a key role in improving and protecting the health of their citizens.